Identification of hepatitis delta virus genotype 3 in andean and amazonian communities of Peru - Balbuena-Torres, Johanna Nery (2023)
Introduction. The Hepatitis Delta Virus (HDV) is the cause of the most severe form of human viral hepatitis and is associated with a high risk of liver fibrosis and hepatocellular carcinoma (HCC). There are 8 HDV genotypes with different geographic distribution. Objectives. To identify the genotypes of VHD circulating in Huanta and three indigenous peoples of the Peruvian Amazon. Methods. Observational and cross-sectional study, from 582 reactive samples for anti-HBc-HBV. Anti-HDV positive samples were processed with the nRT-PCR method, genotype was determined by direct Sanger-type sequencing and   phylogenetic analysis of the R0 fragment. 111 reference sequences from GenBank were used. The 42 sequences of the study were edited y assembled with the bioinformatics programs. Phylogenetic and evolutionary analysis was performed   with the following software: Beast v2.5.2, Jmodeltest v2.1.10, Tracer v1.7.1, Tree Annotator and Figtree v1.4.4. The Bayesian Yule and Birth Death skyline serial models were used, the MCMC at 30 and 80 million respectively, with the relaxed uncorrelated Exponential molecular clock. Summary and central tendency measures were calculated using the program in STATA 14.0. Results. The mean age was 38 years, 52.8% were women. 101 samples were positive for anti-HDV antibodies. HDV RNA was detected in 49.5% of the anti-HDV ELISA reactive samples. Phylogenetic analysis determined the presence of genotype 3. Conclusions. The presence of HDV genotype 3 in Andean and Amazonian communities of Peru is evidenced.